2016
DOI: 10.1177/1932296816682031
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Variability and Its Association With Demographics and Lifestyles in a General Adult Population

Abstract: Objective:The objective was to investigate glycemic variability indices in relation to demographic factors and common environmental lifestyles in a general adult population.Methods:The A Estrada Glycation and Inflammation Study is a cross-sectional study covering 1516 participants selected by sampling of the population aged 18 years and over. A subsample of 622 individuals participated in the Glycation project, which included continuous glucose monitoring procedures. Five glycemic variability indices were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 32 publications
(58 reference statements)
7
42
2
Order By: Relevance
“…In the present study, median MAGE in the non-DM patients seems to be higher than those in earlier reports [ 31 33 ]. Zhou et al and Gude et al have reported that median MAGE for non-DM subjects was 31 mg/dl and 26 mg/dl, respectively.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…In the present study, median MAGE in the non-DM patients seems to be higher than those in earlier reports [ 31 33 ]. Zhou et al and Gude et al have reported that median MAGE for non-DM subjects was 31 mg/dl and 26 mg/dl, respectively.…”
Section: Discussioncontrasting
confidence: 90%
“…MAGE may be influenced by concomitant diseases, since MAGE for non-DM patients with coronary artery disease was reported to be high (60.1±32.9 mg/dl) [ 34 ]. Since non-DM patients in the present study were older and had high rates of history of metabolic and cardiac diseases ( Table 1 ), MAGE in this group was relatively higher than that in the healthy control subjects in the previous reports [ 31 33 ].…”
Section: Discussionmentioning
confidence: 50%
“…In fact, in youth with T1D, higher BMI and adiposity may relate to increased hyperglycemic excursions . Moreover, a cross‐sectional study, which analysed continuous glucose monitoring (CGM) data from a general adult population (12% had been previously diagnosed with diabetes), showed that mean absolute glucose was negatively associated with BMI, while GV indexes were positively associated with aging . Interestingly, no gender difference in GV parameters was observed in the latter study.…”
Section: Phenotype Influence On Glycemic Variabilitymentioning
confidence: 83%
“…AEGIS is a cross‐sectional population‐based study being performed in the municipality of A Estrada (NW, Spain); the data collection and recruiting phase were completed in March 2015. Its aim is to investigate the association between glycation, inflammation, lifestyles, and their association with common diseases and to study discordances between markers for glycaemia . An outline of the AEGIS study is available at www.clinicaltrials.gov, code NCT01796184.…”
Section: Glycation Data Setmentioning
confidence: 99%
“…Its aim is to investigate the association between glycation, inflammation, lifestyles, and their association with common diseases and to study discordances between markers for glycaemia. 18 An outline of the AEGIS study is available at www.clinicaltrials.gov, code NCT01796184. The study was reviewed and approved by the Clinical Research Ethics Committee from Galicia, Spain (CEIC2012-025).…”
Section: Glycation Data Setmentioning
confidence: 99%